Doctor, I have cancer : can you help me? - Peng Tiam, Ang (SNP Editions, 2006)
Doctor, I have cancer. Can you help me? This is a question that Dr Ang Peng Tiam has heard numerous times over the course of his distinguished career as one of Asia's leading oncologists. This book shows the human face of cancer, relating the journey of a dozen patients - facing their diagnoses, struggling with medical jargon, trying alternative therapies and, a for few, finding out how many months they have left to do everything they had always wanted. Some beat the odds, others don't. But their stories reveal hope, strength and, ultimately, grace in the face of despair. Written simply and compassionately, with characteristic humour and a rare insight into his patients' lives, Dr Ang explains the truth behind the many medical aspects of cancer and demonstrates that medicine is not only about finding a cure, but beating the disease - on our own terms.